2022
DOI: 10.1371/journal.pone.0266195
|View full text |Cite
|
Sign up to set email alerts
|

Movement patterns of the functional reach test do not reflect physical function in healthy young and older participants

Abstract: The relationship of the Functional Reach Test (FRT) value with the Center of Pressure Excursion (COPE) and physical function remains unclear, and would be influenced by different population characteristics and movement patterns used in the FRT. Therefore, we explored the relationship between the FRT value and the COPE and physical function in healthy young and older individuals classified according to movement patterns. In 21 healthy young participants (42 sides) and 20 older participants (40 sides), three-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
(78 reference statements)
0
8
0
Order By: Relevance
“… Moriyama et al (2022) examined the relationship between the FRT movement patterns and physical function in healthy young and older adults. The authors used tests that measured lower extremity muscle strength, balance, and gait speed to evaluate physical processes.…”
Section: Resultsmentioning
confidence: 99%
“… Moriyama et al (2022) examined the relationship between the FRT movement patterns and physical function in healthy young and older adults. The authors used tests that measured lower extremity muscle strength, balance, and gait speed to evaluate physical processes.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to the measurement, all participants were instructed to be barefoot, shirtless, and to wear spandex shorts in their underclothes. Markers with a diameter of 9 mm were applied to 67 locations on each subject’s entire body, following the Plug-in Gait Full-Body model ( https://www.vicon.com/ ) ( Fig 2 ) for the upper body, thighs and lower legs, and the multi-segment foot model method [ 28 , 29 ] ( Fig 3 ) for the feet. Motion analysis was performed using a three-dimensional motion analysis system (Vicon Nexus, Oxford, London, UK) with twelve infrared cameras with a sampling frequency of 100 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…The missing parts of the marker trajectory data were completed by the gap-filling function in Vicon. Marker trajectory data and ground reaction force data were smoothed using the Butter worth filter in Vicon, with reference to a previous study [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, the functional reach test (FRT) has been used to evaluate SBA in older adults 5 , 6 , 7 ) . Mitani et al 8 ) reported a positive correlation between the reach distance and the length of movement of the center of pressure (LMCOP), and the FRT is considered a valid tool for evaluating the stability limits 9 ) . Furthermore, the FRT is associated with reach distance and the risk of falling 10 , 11 ) , and a cutoff value of approximately 6 inches (15.2 cm) to identify individuals at high risk of falling in previous studies in Western populations 10 ) .…”
Section: Introductionmentioning
confidence: 99%